2012
DOI: 10.1038/nrmicro2910
|View full text |Cite
|
Sign up to set email alerts
|

Microbial life in the phyllosphere

Abstract: Our knowledge of the microbiology of the phyllosphere, or the aerial parts of plants, has historically lagged behind our knowledge of the microbiology of the rhizosphere, or the below-ground habitat of plants, particularly with respect to fundamental questions such as which microorganisms are present and what they do there. In recent years, however, this has begun to change. Cultivation-independent studies have revealed that a few bacterial phyla predominate in the phyllosphere of different plants and that pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

59
1,717
1
33

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,760 publications
(1,810 citation statements)
references
References 151 publications
59
1,717
1
33
Order By: Relevance
“…Co-correlation patterns among bacterial and fungal indicator OTUs revealed that indicator OTUs characteristic of atmospheric deposition did not share the same habitats as the other indicator OTUs. In addition, bacterial and fungal OTUs characterizing atmospheric deposition (rain and aeolian dust) consisted of either pathogenic epiphytic (Aureobasidium) or highly versatile microorganisms (Methylobacterium, Pseudomonas and Sphingomonas) predominantly associated with plants (Vorholt, 2012). Representatives of these bacterial genera have also been found in cloud droplets (Amato et al, 2005), in hailstones (Šantl-Temkiv et al, 2012) and in aerosols collected at high altitude (Bowers et al, 2012).…”
Section: Origin Of Microbial Pioneers In Deglaciated Soilsmentioning
confidence: 93%
“…Co-correlation patterns among bacterial and fungal indicator OTUs revealed that indicator OTUs characteristic of atmospheric deposition did not share the same habitats as the other indicator OTUs. In addition, bacterial and fungal OTUs characterizing atmospheric deposition (rain and aeolian dust) consisted of either pathogenic epiphytic (Aureobasidium) or highly versatile microorganisms (Methylobacterium, Pseudomonas and Sphingomonas) predominantly associated with plants (Vorholt, 2012). Representatives of these bacterial genera have also been found in cloud droplets (Amato et al, 2005), in hailstones (Šantl-Temkiv et al, 2012) and in aerosols collected at high altitude (Bowers et al, 2012).…”
Section: Origin Of Microbial Pioneers In Deglaciated Soilsmentioning
confidence: 93%
“…The above-ground parts of plants, and called phyllosphere, are colonized by a diverse microbial community that can inhabit the interior of plant tissues (as endophytes) as well as plant's surface (as epiphytes) (Vorholt, 2012). Recent studies indicate that host plant genotype can influence the microbiome composition by acting on keystone species, which in turn affects plant colonization by many other microbes (Agler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The authors stressed the need for studies on the functional consequences of changes in microbial community structure and the mechanisms by which plants control the microbial populations on their aerial plant surfaces. The composition of microbial populations in the phyllosphere are also influenced by environmental factors, such as, UV, humidity, temperature, geographical location (Rastogi et al, 2012;Vorholt, 2012;Rastogi et al, 2013), nitrogen fertilization (Ikeda et al, 2011), and pesticide treatments (Zhang et al, 2009;Moulas et al, 2013).…”
Section: The Role Of the Microbiome In Fruit Health And Disease à A Nmentioning
confidence: 99%
“…Studies on plant microbiomes (phytobiomes) in both the phyllosphere and rhizosphere indicate that plants should be considered as "super organisms" where very diverse microbial communities provide specific functions and traits to plants (Vorholt, 2012;de Bruijn, 2013). These functions include five key features: (1) improving nutrient acquisition and growth, (2) sustaining plant growth under biotic and/or abiotic stress, (3) inducing resistance against pathogens, (4) interacting with plant or human pathogens, and (5) interacting with other trophic levels, such as insects.…”
Section: The Role Of the Microbiome In Fruit Health And Disease à A Nmentioning
confidence: 99%